2018
DOI: 10.1371/journal.pone.0208038
|View full text |Cite
|
Sign up to set email alerts
|

Role of CTRP3, CTRP9 and MCP-1 for the evaluation of T2DM associated coronary artery disease in Egyptian postmenopausal females

Abstract: C1q complement/tumor necrosis factor (TNF)—related protein (CTRP) family comprises of 15 proteins that posses important implications in energy homeostasis, infection and inflammation. However, their roles in diabetes mellitus (DM) and its vascular complications have not been completely assessed. This works aims to study the association of two CTRPs; 3 and 9, with pro-inflammatory cytokine monocyte chemoattractant protein-1 (MCP-1), and biochemical parameters of type 2 diabetes (T2D), dyslipidemia and coronary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 23 publications
(30 reference statements)
3
14
0
1
Order By: Relevance
“…In contrast, MCP-1 knockout mice and inhibition of MCP-1 activity exhibited improvements in insulin resistance and hepatic steatosis (96, 97). Consistent with the findings in mice, humans show increased plasma levels of MCP-1 in T2D (98).…”
Section: Monocyte Chemotactic Protein 1 (Mcp-1)supporting
confidence: 85%
“…In contrast, MCP-1 knockout mice and inhibition of MCP-1 activity exhibited improvements in insulin resistance and hepatic steatosis (96, 97). Consistent with the findings in mice, humans show increased plasma levels of MCP-1 in T2D (98).…”
Section: Monocyte Chemotactic Protein 1 (Mcp-1)supporting
confidence: 85%
“…The inflammatory response is one of major causes of myocardial damage. The levels of inflammatory factors and chemokines in the myocardial tissue are elevated rapidly after myocardial injury in AMI, further exacerbate the inflammatory response and aggravate myocardial infarction, ventricular remodeling, and other forms of cardiac dysfunction ( Ahmed et al, 2018 ). In this study, the levels of inflammatory factors CRP, and myocardial markers such as CK and CK-MB, were significantly lower in the Xinmailong group compared with the control group, suggesting that Xinmailong injection has certain anti-inflammatory effects and protect against myocardial damage.…”
Section: Discussionmentioning
confidence: 99%
“…In an earlier study, Wang et al reported that both CTRP9 levels in serum and CTRP9 mRNA expression in epicardial adipose tissue were decreased in coronary artery disease (CAD) patients compared with non‐CAD patients (Wang et al, 2015; Yu et al, 2018). In a study of postmenopausal women, Ahmed et al (2018) found that CTRP9 levels were decreased in both T2DM and CAD and further decreased in T2DM patients with CAD. Moreover, in patients with chronic heart failure and reduced ejection fraction, plasma CTRP9 levels were observed to be decreased compared with control patients, and CTRP levels were gradually reduced in the New York Heart Association (NYHA) functional Class II, NYHA III, and NYHA IV groups and positively correlated with left ventricular ejection fraction (LVEF) but negatively correlated with N‐terminal pro‐brain natriuretic peptide (NT‐proBNP; Gao et al, 2019).…”
Section: Discussionmentioning
confidence: 99%